2020
DOI: 10.1089/bari.2019.0043
|View full text |Cite
|
Sign up to set email alerts
|

Does Bariatric Surgery Increase the Formation of Parathyroid Adenoma

Abstract: Background: Bariatric surgery is an important treatment option of obesity over the last decade. While bariatric surgery reduces weight and helps maintanence, it significantly reduces the obesity-related comorbidities, as well. Secondary hyperparathyroidism is a common metabolic complication of bariatric surgery, despite the recommended dose of calcium and vitamin D replacement. We have presented in our article that one of the results of bariatric surgery may be parathyroid adenoma (PA), although the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The mechanism resides in calcium malabsorption which, in association with vitamin D deficiency, promotes secondary hyperparathyroidism leading to bone resorption. There are even claims that, in the very long term, post-bariatric surgery hypocalcemia may overstimulate parathyroid gland and lead to the anectodical development of a parathyroid adenoma ( 40 ). Further, intestinal adaptation mechanisms, local effect of the Wnt/β-catenin signaling pathway, changes in carrier proteins, and the effect of adipokines are other calcium-related mechanisms potentially involved in bone loss after bariatric surgery ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism resides in calcium malabsorption which, in association with vitamin D deficiency, promotes secondary hyperparathyroidism leading to bone resorption. There are even claims that, in the very long term, post-bariatric surgery hypocalcemia may overstimulate parathyroid gland and lead to the anectodical development of a parathyroid adenoma ( 40 ). Further, intestinal adaptation mechanisms, local effect of the Wnt/β-catenin signaling pathway, changes in carrier proteins, and the effect of adipokines are other calcium-related mechanisms potentially involved in bone loss after bariatric surgery ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…While bariatric procedures are well known to be associated with secondary hyperparathyroidism [24][25][26][27], recent studies suggest that bariatric surgery may also raise the risk of developing primary hyperparathyroidism (PHP) and the formation of parathyroid adenomas [9][10][11][12][13][14]. Keskin et al reported ve cases of PHP in patients who underwent prior SG, and suggested that there may be a relationship between bariatric surgery and PHP [13]. In the present study, 1.5% of patients in our cohort with PHP who underwent parathyroidectomy had a history of bariatric surgery, which is evidence that this is a clinically relevant population.…”
Section: Discussionmentioning
confidence: 99%
“…The number of bariatric operations being performed is increasing [8]. There are reports of patients who are post-bariatric surgery going on to develop endocrine abnormalities of the thyroid and parathyroid glands, including primary hyperparathyroidism (PHP) [9][10][11][12][13][14]. Although there is a growing body of literature supporting that patients with a history of bariatric surgery who undergo subsequent thyroidectomy are at increased risk for hypocalcemia [15,16], hypocalcemia after parathyroidectomy is not well-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there have been reports of PHPT with hypercalcemia after RYBG [ 42 ]. These cases may represent classical PHPT in a patient with RYGB or tertiary hyperparathyroidism in patients with prolonged PTH stimulation somewhat akin to kidney disease [ 43 ].…”
Section: Casesmentioning
confidence: 99%